Consensus recommendations on the role of nurses in the care of headache patients: protocol for a european e-delphi study - Annette Vangaa Rasmussen; Rigmor Hoejland Jensen; Leena Eklund Karlsson; Louise Schlosser Mose (BMC, 2023)
Abstract Background Nurses play an important role in the treatment of headache patients at the specialized headache centers in Europe, however, a unified definition of nursing tasks and conduction of tasks is lacking. The objective of this e-Delphi study is twofold. Initially, to obtain healthcare professional headache experts' opinions on which tasks are associated with nurses' care in migraine treatment. Then, through an iterative multi-staged process, to combine the opinions into group consensus statements and develop evident European nursing recommendations for migraine treatment. Methods In Delphi studies there are no unambiguous methodological guidelines and this protocol is being published to ensure transparency and quality in the study process. We invite nurses working in specialized headache centers and neurologists co-working with nurses in Finland, Denmark, Norway, Sweden, United Kingdom, Netherlands, Germany, Ireland, Estonia and Switzerland to participate anonymously in the expert panel. This e-Delphi study consists of three rounds of online questionnaires. We use Open-ended questions to capture the essentials of nurse tasks as understood by the expert panel members. Data are analyzed using content analysis. Predefined statements are applied for the experts to rate the importance of nurses' tasks synthesized from a systematic examination of the existing literature. Consensus is measured using descriptive statistics; median, Interquartile range (IQR) and percentage agreement. Measurement of agreement between participants will be analyzed using inferential statistics; Kendall's coefficient and stability between rounds; Wilcoxon rank-sum test. Statements, which receive consensus in the third round, are included in the final compilation of European recommendations for nurse care for migraine patients. Discussion The e-Delphi study will provide European recommendations on nurse care in migraine treatment, which could not be created on the basis of the existing literature. The recommendations can open for the conduction of further research including measurement of efficacy of clinical implementation of the recommended tasks. Trial registration The study is registered at The Region of Southern Denmark (21/52,885). According to The Regional Ethical Committee and Danish law, no additional approval is relevant (20212000-145). A written informed consent is obtained from all participants before inclusion in the study.